Debating controversial issues in order to educate citizens. An experience with high school students (Praxis Educativa, 2017)
This paper presents the results of an action-research project conducted in Chile, in 2015, which has inquired about the potential of controversial issues debate for the development of citizenship skills. Specifically, seventyfour secondary school students, aged between 14 and 15 years old, have researched and debated about the possibledecriminalization of marijuana in Chile and about the Bolivian maritime claim, against the Chilean government, at the International Court of Justice located in The Hague (Netherlands). The results show the big potential of such issues for the development of citizenship skills, a high positive evaluation of this method by students and the need to incorporate these kinds of issues in the new Chilean citizenship subject
Keywords: citizenship education; controversial issues; social problems; debate; democracy